PENGARUH PENGETAHUAN DAN SOSIALISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP EFEKTIVITAS PEMANFAATAN TEKNOLOGI INFORMASI PERPAJAKAN BAGI WAJIB PAJAK ORANG PRIBADI - Mandasari, Yanti; Risa, Nurma (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2013)
This study examines the influences of knowledge and sosialization of tax administration system on theeffectiveness of using tax information technology for individual tax prayer. The responden areindividual tax-payers in Bekasi area. Hypothesis test using t-test and F-test. And data analysis usingregression. The results determine that knowledge and sosialization positive and significantly influencethe effectiveness using tax information technology. It means that tax payers will use technologyinformation if they have enough knowledge about tax administration system.